Exploring the applicability of a multifactor mindfulness scale in the Chinese college context - Zhang, Dan; Shen, Jianbo; Ma, Hongyu (Frontiers in Psychology, 2024)
The development of a precise and comprehensive mindfulness measurement tool is a compelling area of research due to its lack at present. This study examines the utility of a multifactor mindfulness scale, particularly the Chinese version of the Comprehensive Inventory of Mindfulness Experiences (CHIME), among Chinese college students. Prior to formal testing, 410 subjects completed the CHIME-37, providing feedback for refinement. During formal assessment, 1,785 subjects participated, with 490 students retested after two months. The validity of the CHIME-37 was evaluated using various scales, including subjective well-being, psychological well-being, peace of mind, self-reflection, insight, emotion regulation, depression-anxiety-stress, and sickness questionnaire. In exploratory factor analysis of Sample 1 (n = 838), CHIME revealed 8 factors, explaining 70.696% of the variance. Confirmatory factor analysis in Sample 2 (n = 947) confirmed the 8-factor model's validity. Internal consistency coefficients ranged from 0.848 to 0.914, with test-retest reliabilities ranging from 0.746 to 0.885, and split-half reliabilities ranging from 0.795 to 0.898. Total and dimension scores correlated positively with subjective well-being, psychological well-being, emotion stability, and cognitive reappraisal (P < 0.01) but negatively with physical and mental illnesses, depression-anxiety-stress, and expressive inhibition (P < 0.01). The revised CHIME demonstrates robust reliability and validity, establishing it as a suitable tool for measuring the mindfulness levels of Chinese college students.